Epidemiology and factors of tuberculosis treatment outcome, Bangladesh, 2012-13 - Sultana, Rabeya; Rahman, Mojibur; Rahman, Mahmudur (International Journal Of Community Medicine And Public Health, 2021)
Tuberculosis (TB) treatment outcome is an important indicator to improve TB control efforts. We assessed factors associated with unfavorable treatment outcomes among smear-positive pulmonary TB patients reported to the national TB program from January 2012 to December 2013 in Bangladesh. Favorable outcomes were cured and treatment completed with unfavorable outcomes as failed, defaulted, died and lost to follow-up. We retrieved 98,932 patients with outcome data; 65,458 (66%) were male and 7,956 (8%) had unfavorable outcomes (3,737 (47%) died, 1,641 (21%) defaulted, and 1,599 (20%) lost to follow-up). In multivariable analysis, male gender (adjusted odds ratio [aOR] 1.41; 95% confidence interval [CI] 1.34-1.49) and treatment at a chest disease hospital (CDH) (aOR 1.44; 95% CI 1.25-1.66) were risk factors. The association between male gender and unfavorable outcomes may result from the high smoking rates among males in Bangladesh. The association of treatment at a CDH with unfavorable outcomes may occur because complicated cases (e.g., TB with co-infections) are usually treated in a chest hospital in Bangladesh. A case-control study could further confirm and explain these findings.